2014
DOI: 10.1002/wsb.503
|View full text |Cite
|
Sign up to set email alerts
|

Trends in male wild turkey abundance and harvest following restoration efforts in the southeast region of Missouri, 1960–2010

Abstract: Long-term estimates of abundance can be useful in elucidating wildlife population and hunter dynamics as well as other potential factors affecting populations. We used estimated vulnerability coefficients from a statistical population reconstruction (SPR) analysis (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), along with a 50-year time series of harvest and hunter-effort data to reconstruct a male wild turkey (Meleagris gallopavo) population in southeastern Missouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Higher removal probabilities for adult males than for juvenile males were also anticipated, as multiple studies reported that adult males are more vulnerable to harvest than juveniles (Vangilder 1992, Healy and Powell 2000, Chamberlain et al, 2012). Previous research also suggested harvest rates for males might vary among management regions (Diefenbach et al 2012), which would be expected even in the absence of spatially heterogeneous capture probabilities given variation of hunter effort in space (Clawsen et al 2015, Stevens et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Higher removal probabilities for adult males than for juvenile males were also anticipated, as multiple studies reported that adult males are more vulnerable to harvest than juveniles (Vangilder 1992, Healy and Powell 2000, Chamberlain et al, 2012). Previous research also suggested harvest rates for males might vary among management regions (Diefenbach et al 2012), which would be expected even in the absence of spatially heterogeneous capture probabilities given variation of hunter effort in space (Clawsen et al 2015, Stevens et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Turkey hunting participation and harvest are considerably larger for the spring season in most areas (Ericksen et al , Parent et al ), and spring harvest has commonly been used as an index to population size (Lint et al , Healy and Powell , Parent et al ). Recent efforts to develop statistically rigorous estimates of abundance at management scales have also used data from spring harvest, and consequently produced estimates of abundance at the start of spring hunting for the male segment of the population (Diefenbach et al , St. Clair et al , Clawson et al ). Thus, our simulations assumed male abundances were used to set fall harvest targets because data needed to estimate female abundance is not typically available.…”
Section: Methodsmentioning
confidence: 99%
“…Populations in many areas now appear to be either stable or declining slowly (Ericksen et al 2016). With some notable exceptions (e.g., Clawsen et al 2015), monitoring data necessary to employ statistical abundance estimation techniques are not available at the broad spatial scales at which Turkeys are managed. With some notable exceptions (e.g., Clawsen et al 2015), monitoring data necessary to employ statistical abundance estimation techniques are not available at the broad spatial scales at which Turkeys are managed.…”
Section: Case Study With Wild Turkeysmentioning
confidence: 99%
“…However, management in most states proceeds with highly uncertain information on the status of local populations. With some notable exceptions (e.g., Clawsen et al 2015), monitoring data necessary to employ statistical abundance estimation techniques are not available at the broad spatial scales at which Turkeys are managed. Harvest-based metrics have been used for several decades to index populations (Healy and Powell 2000); however, the assumptions necessary for these indices to be reliable indicators of spatial-temporal population patterns (i.e., constant hunter effort and/or probability of harvest per unit effort) are either known or likely to be false (Harris 2010.…”
Section: Case Study With Wild Turkeysmentioning
confidence: 99%